John Bull ask'd at Saint Stephens!!! - (:unkn) unknown (Fores, S. W., 1800)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Ireland -- History -- Union, 1801; John Bull (Symbolic character)